The Impact of Green Marketing on Strategic Awareness: An Analytical Examination of Perspectives from Administrators, Academics, and Students at the University of Raparin - Abdalrahman Khoshnaw, Kamaran; Othman, Bestoon (JBS Nexus, 2026)
This study examined the impact of green marketing on strategic awareness among university administrators, faculty, and students. Three aspects of green marketing were specifically examined: (1) environmental protection, (2) customer satisfaction, and (3) organizational profitability. Data from 365 participants, including administrators, professors, and students, were gathered using a quantitative research approach to investigate the connection between strategic awareness and green marketing strategies. The data were analyzed using smart Partial Least Squares (PLS) structural equation modeling (SEM), which enabled reliable evaluation of the proposed correlations. The results show that strategic awareness is greatly influenced by all three aspects of green marketing, with environmental preservation having the greatest influence. Furthermore, this study emphasizes how consumer happiness can strengthen the link between strategic awareness and green marketing. These findings highlight the importance of incorporating green marketing concepts into institutional plans to promote a culture of sustainable and strategic thinking. In addition to offering useful advice for colleges to match their operations with sustainable development objectives and raise stakeholder strategic awareness, this study adds to the expanding corpus of research on green marketing in higher education.